FORMING OF DIASTEREOISOMER WITH L-ISOLEUCIN TO SEPARATE OFLOXACIN ENANTIOMER USING PREPARATIVE LIQUID CHROMATOGRAPHY - Diana Hendrati; Husein H. Bahti; Uji Pratomo; Zenith Putri Dewianti (Departemen Kimia, 2015)
Ofloxacin is an antibiotic with a broad range of uses in human and veterinary medicine to prevent or treat bacterial infections which has an enantiomeric mixture structure of (-)-ofloxacin and (+)-ofloxacin. Enantiomers of drugs have different pharmacology and toxicology effects that need to be separated before it used to get the molecule target. Separation of enantiomers using chiral column is not quite economical separation, but the separation of enantiomers using a chiral column by converting the enantiomeric mixture into a diastereoisomeric form is the right solution. This study aims to separate mixture of ofloxacin enantiomers by forming diastereoisomeric with L-isoleusine and copper (II) into compound (-)-ofloxacin and (+)-ofloxacin and also to identify the optimum condition of separation using HPLC with preparative liquid chromatography column. Samples injected into the column and eluted by the mobile phase (consisting a mixture of water-methanol (88:12) and solution of L-isoleusine 4 mM and copper (II) sulfate 9 mM). Then the fractions were compared with the standard and the purity was tested by HPLC. This research resulted 47 fractions which four of early fractions have correspond with the standard of (-)-ofloxacin and 43 other factions do not. We obtained the resolution of this separtion about 0.98. The small resolution caused by complex formation is not perfect with the concentration of L-isoleucine and copper (II).